Multicenter experience with andexanet alfa for refractory pericardial bleeding during catheter ablation of atrial fibrillation. (8th January 2023) - Zghaib, Tarek; Allison, John D.; Barrett, Christopher; Arkles, Jeffrey; D'Souza, Benjamin; Luebbert, Jeffrey; Garcia, Fermin; Heist, E. Kevin; Tzou, Wendy; Callans, David; Marchlinski, Francis E.; Frankel, David S.
Abstract: Introduction: Pericardial bleeding is a rare but life‐threatening complication of atrial fibrillation (AF) ablation. Patients taking uninterrupted oral anticoagulation (AC) may be at increased risk for refractory bleeding despite pericardiocentesis and administration of protamine. In such cases, andexanet alfa can be given to reverse rivaroxaban or apixaban. In this study, we aim to describe the rate of acute hemostasis and thromboembolic complications with andexanet for refractory pericardial bleeding during AF ablation. Methods and Results: In this multicenter, case series, participating centers identified patients who received a dose of apixaban or rivaroxaban within 24 h of AF ablation, developed refractory pericardial bleeding during the procedure despite pericardiocentesis and administration of protamine and received andexanet. Eleven patients met inclusion criteria, with mean age of 73.5 ± 5.3 years and median CHA2 DS2 ‐VASc score 4 [3–5]. All patients received protamine and pericardiocentesis, and 9 (82%) received blood products. All patients received a bolus of andexanet followed, in all but one, by a 2‐h infusion. Acute hemostasis was achieved in eight patients (73%) while three required emergent surgery. One patient (9%) experienced acute ST‐elevation myocardial infarction after receiving andexanet. Therapeutic AC was restarted after a mean of 2.2 ± 1.9 days and oral AC was restarted after a mean of 2.9 ± 1.6 days, with no recurrent bleeding. Conclusion: In patients on uninterrupted apixaban or rivaroxaban, who develop refractory pericardial bleeding during AF ablation, andexanet can achieve hemostasis thereby avoiding the need for emergent surgery. However, there is a risk of thromboembolism following administration.